Relationship Violence During The Covid-19 Pandemic: A Systematic Literature Review - Obadyah, Ariel Barlian; Susilo, Daniel; Anugerah, Cendera Rizky; Karina, Vega; Kustiwa, Agus (Tuturlogi: Journal of Southeast Asian Communication, 2024)
This systematic literature review aims to analyze various studies on relationship violence during the COVID-19 pandemic. Data collection was conducted with sources from Crossref between 2020 and 2022. The keywords used were "domestic violence," "intimate partner violence," "gender-based violence," and "sexual violence." From this search found thirty articles related to the topic. The results showed increased violence in relationships during the COVID-19 pandemic in various countries, with forms of violence being emotional, physical, verbal, sexual, and financial. The underlying factors are economic pressure, social isolation, difficulty and unwillingness to seek help, and sociocultural factors that favor violence. Meanwhile, the way to overcome this is through strengthening community relations, increasing ease of access to health care, government economic assistance, and improving information and communication technology for access to help and information. Another result found was a reluctance on the part of victims to seek help due to fear, shame, distrust of the authorities, and local culture and social norms.